E-Selectin Mediates Immune Cell Trafficking in Corneal Transplantation. Issue 4 (April 2016) - Dohlman, Thomas H.; Di Zazzo, Antonio; Omoto, Masahiro; Hua, Jing; Ding, Julia; Hamrah, Pedram; Chauhan, Sunil K.; Dana, Reza
Abstract : Background: Immune rejection continues to threaten all tissue transplants. Here we sought to determine whether platelet (P)- and endothelial (E)-selectin mediate T cell recruitment in corneal transplantation and whether their blockade can reduce T cell graft infiltration and improve long-term corneal allograft survival. Methods: In a murine model of allogeneic corneal transplantation, we used PCR and immunohistochemistry to investigate expression of P- and E-selectin in rejected versus accepted allografts and lymph node flow cytometry to assess expression of selectin ligands by effector T cells. Using P- and E-selectin neutralizing antibodies, we evaluated the effect of blockade on CD4 T cell recruitment, as well as the effect of anti–E-selectin on long-term allograft survival. Results: The P- (93.3-fold, P < 0.05) and E-selectin (17.1-fold, P < 0.005) are upregulated in rejected versus accepted allogeneic transplants. Type 1 T helper cells from hosts with accepted and rejected grafts express high levels of P-selectin glycoprotein ligand 1 and glycosylated CD43. In vivo blockade of P (0.47 ± 0.03, P < 0.05) and E selectin (0.49 ± 0.1, P < 0.05) reduced the number of recruited T cells compared with IgG control (0.98 ± 0.1). Anti–E-selectin reduced the number of mature antigen-presenting cells trafficking to lymphoid tissue compared with control (6.96 ± 0.9 vs 12.67 ± 0.5, P < 0.05). Anti–E-selectin treatment delayed graft rejection and increased survival compared with control, although this difference did not reach statistical significance. Conclusions: In a model of corneal transplantation, P- and E-selectin mediate T cell recruitment to the graft, E-selectin mediates APC trafficking to lymphoid tissue, and blockade of E-selectin has a modest effect on improving long-term graft survival. Abstract : In a murine model of allogeneic corneal transplantation, P-and E-selectin are upregulated in rejected transplants. Host Th1 cells express high levels of PSGL-1 and CD43. In vivo anti-P and anti-E selectin reduce recruited T cells. Anti-E-selectin treatment delay graft rejection although it does not reach statistical significance.